The social and ethical issue of labor on the 40th anniversary of laborem exercens - Ortega Cabrera, Agustín (2021)
This article studies and investigates the socio-historical and ethical reality of labor, commemorating the 40th anniversary of the encyclical Laborem exercens (LE), written by Saint John Paul II. In this way, it intends to expose the actuality of the social and moral teaching of the faith and the church, along with Popes like Francis, who continues to delve into these social and ethical questions about labor. To do this, it uses the methodology of the theology and social doctrine of the church (DSI), with its interdisciplinary perspective, analyzing in an interdisciplinary way the reality of labor and the state of said issue, with studies or significant authors in this regard, in dialogue with the social or human sciences and philosophy, and with social movements such as the labor movement.